2010
DOI: 10.1002/cne.22249
|View full text |Cite
|
Sign up to set email alerts
|

Comparative anatomy of the locus coeruleus in humans and nonhuman primates

Abstract: The locus coeruleus (LC) is a dense cluster of neurons that projects axons throughout the neuroaxis and is located in the rostral pontine tegmentum extending from the level of the inferior colliculus to the motor nucleus of the trigeminal nerve. LC neurons are lost in the course of several neurodegenerative disorders, including Alzheimer's and Parkinson's diseases. In this study, we used Nissl staining and tyrosine hydroxylase (TH) immunoreactivity to compare the human LC with that of closely related primate s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 87 publications
1
40
1
1
Order By: Relevance
“…Stereological analysis of NeuN immunostaining revealed that there were ~67.5 million WMICs within the infracortical white matter of the lar gibbon. This is not an insignificant number of neurons, as many neural systems within the brain with far fewer neurons, for example, the locus coeruleus complex (e.g., Aston‐Jones & Cohen, ; Chan‐Palay & Asan, ; Sharma et al, ), exert a tremendous influence over function across the entire brain. Moreover, the number of WMIC in the lar gibbon is three times the number of neurons found in the entire cerebral cortex of one of the smallest primates, Microcebus murinus (Herculano‐Houzel, Catania, Manger, & Kaas, ).…”
Section: Discussionmentioning
confidence: 99%
“…Stereological analysis of NeuN immunostaining revealed that there were ~67.5 million WMICs within the infracortical white matter of the lar gibbon. This is not an insignificant number of neurons, as many neural systems within the brain with far fewer neurons, for example, the locus coeruleus complex (e.g., Aston‐Jones & Cohen, ; Chan‐Palay & Asan, ; Sharma et al, ), exert a tremendous influence over function across the entire brain. Moreover, the number of WMIC in the lar gibbon is three times the number of neurons found in the entire cerebral cortex of one of the smallest primates, Microcebus murinus (Herculano‐Houzel, Catania, Manger, & Kaas, ).…”
Section: Discussionmentioning
confidence: 99%
“…IC units exhibited clear responses to auditory stimuli. LC+ units, which likely came from sites in either the LC or the adjacent, NE-containing subcoeruleus nucleus (Sharma et al, 2010; Paxinos et al, 2008; Kalwani et al, 2014), had relatively long action-potential waveforms, were sensitive to arousing external stimuli (e.g., door knocking), and decreased firing when the monkey was drowsy (e.g., eyelids drooped) (Aston-Jones et al, 1994; Bouret and Sara, 2004; Bouret and Richmond, 2009). These sites were verified using MRI and assessing the effects of systemic injection of clonidine on LC+ responses in both monkeys, and histology with electrolytic lesions and electrode-tract reconstruction in monkey Oz.…”
Section: Methodsmentioning
confidence: 99%
“…(C) Negative deviations from regression line for striatum and amygdaloid nuclei in humans [with permission]. (D) Human LC (vertical axis) shows fewer neurons than expected by comparison to neocortex volume (horizontal axis); TH = tyrosine hydroxylase [with permission]. (E) Diagram showing the evolutionarily conserved functional module of the motor loop and subsequent “copy paste” of this module for other functions by the exaptation principle.…”
Section: Humans and Telencephalizationmentioning
confidence: 99%
“…When compared to the cerebral cortex, the total number of locus coeruleus (LC) neurons is substantially lower than expected in humans (Fig. D) . The olfactory bulb is approximately 30% as large as it should be for a primate brain .…”
Section: Humans and Telencephalizationmentioning
confidence: 99%